2016
DOI: 10.1001/jamasurg.2015.2683
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Airway Pressure Release Ventilation on Dynamic Alveolar Heterogeneity

Abstract: Increasing PEEP during LTVV increased alveolar recruitment and dynamic homogeneity but had a significantly different alveolar size distribution compared with the control group. By comparison, reducing the time at low pressure (EEFR to PEFR ratio of 75%) in the APRV group provided dynamic homogeneity and a closer approximation of the dynamics observed in the control group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
113
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(114 citation statements)
references
References 30 publications
0
113
0
1
Order By: Relevance
“…2b). Using these precisely controlled APRV settings, a number of studies have shown that P-APRV recruits and stabilizes the alveoli and alveolar ducts [54][55][56] and reduces the incidence of ARDS in multiple animal models [5,57,62]. A metaanalysis has shown a reduction in ARDS incidence in trauma patients [53].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…2b). Using these precisely controlled APRV settings, a number of studies have shown that P-APRV recruits and stabilizes the alveoli and alveolar ducts [54][55][56] and reduces the incidence of ARDS in multiple animal models [5,57,62]. A metaanalysis has shown a reduction in ARDS incidence in trauma patients [53].…”
Section: Discussionmentioning
confidence: 99%
“…The expiratory flow curve is analyzed, and the ratio of the end-expiratory flow (EEF) to the peak expiratory flow (PEF) is set so that the EEF/PEF ratio is 75 % [5,[49][50][51][52][53][54][55][56][57][58][59][60][61][62] (See figure on previous page.) Fig.…”
Section: How Expiratory Duration Was Personalizedmentioning
confidence: 99%
See 3 more Smart Citations